The Rapid Chain Extension of Anthracene-Functional Polyesters by the Diels-Alder Reaction with Bismaleimides - Kriegel, Robert M.; Saliba, Katie L.; Jones, Genay; Schiraldi, David A.; Collard, David M. (Macromolecular chemistry and physics, 2005)
The chain extension of anthracene end‐capped oligoesters by reaction with bismaleimides constitutes a rapid route to high molecular weight polyesters. Polytransesterification of bis(2‐hydroxyethyl) terephthalate in the presence of a small amount of 2‐hydroxyethyl 2‐anthracenecarboxylate provides low molecular weight anthracene‐terminated macromers with anthracene end group functionality (fAN) of 1.66–1.85. These are subject to rapid chain extension with di(4‐maleimidophenyl)methane by Diels‐Alder cycloadditions resulting in consumption of the anthracene and maleimide end groups to generate polymers with $\overline M _{\rm n}$ > 2.0 × 104 g · mol−1. Thus, generation of the polymeric structure is achieved rapidly by addition reactions rather than sluggish transesterification reactions in which a condensate must be removed from the viscous polymer melt. Chain extension of low‐molecular weight 2‐anthracenecarboxylate terminated oligoesters.